Resource management domains in forestry research - Booth, T.H.; Turnbull, J.W. (1998)
To manage tree plantations or natural forests effectively requires close attention to interactive aspects of environmental, economic social and management factors. Extrapolation of results is crucial to the adoption of research findings and it is important to estimate the extent to which results from specific research sites can be applied to other areas. Resource management domains (RMDs), defined as relatively homogenous tracts of land with inherent suitability for specific uses, can assist in these and other tasks. This paper reviews the use of both intuitive and computerised analyses to define RMDs. Computerised analyses have increased the speed and ease with which alternative options can be examined and evaluated. Climatic mapping programs such as WORLD can be used to assist in the selection of tree species for growing in plantations and GROWEST to provide better agro-ecological patterns using more realistic conditions experienced by plants. A major limitation to the development of environmental domains has been the difficulty in incorporating soils data at the high resolutions often required for GIS analysis. The DOMAIN package that is linked to a GIS and a digital elevation model is well suited to applications where the site locations or environmental data are limited. It is not sensitive to highly covariate data such as climatic data and is potentially a useful tool for determining RMDs. The land system mapping by CSIRO in Australia is an example of intuitive integration of environmental and biological variables into easily defined land units. Other intuitive analyses in Brazil, Canada, South Africa and by FAO are described. The paper concludes that the concept of RMDs and their application to forestry and forestry research is well established but to maximise their value they need to be highly flexible and tailor-made for specific applications.